Unorganized health education: the impact and challenges! - Chinnayan, Sivakumar (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction Achieving better health is everyone’s wish and irrespective of various health practice systems, all attempt to end in good health only. To keep us vigil from ill effects around us, we all seek information which will help us to protect us from dangers of diseases. In the modern world, the medium to get all information is in our hands itself and we exchange oceans of information of different nature. But is these information are genuine to adhere and do we owe the responsibility to protect our fellow being before forwarding a health related information. Methods The author has attempted to find out the attitude and practice of exchanging health related information through social media and attempted to analyze its impact on health seeking behavior. A simple random study was chosen in which 300 respondents were chosen. Results A self-structured interview schedule was administered for collecting the data and through scientific data analysis it was found that majority of the respondents exchange health related information through different social medias. It was also found that majority of the respondents forward health related information irrespective of the genuineness of the content. Although only a one third of the respondents follow various health tips being shared, it is also an alarming signal for health care providers to look into. Conclusions Sensitizing the public about the organized forms of medical practice is very much needed on one side and controlling the false health related information is a huge challenge on the other side. Owing to individual’s responsibility may save the lives, but using the same medium with appropriate contents will definitely promote the well-being of the nation.